Pengaruh Penerapan Model PjBL dengan Pendekatan STEM Terhadap Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Bangun Ruang Sisi Lengkung di SMP - Nurwati Djam'an; Nur Amaliah; Fajar Arwadi (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the effectiveness of implementing the Project-Based Learning (PjBL) model with a STEM approach in enhancing students' mathematical creative thinking skills on the topic of curved-surface solids. The method used is a pre-experimental design with a one-group pretest-posttest design, involving 33 students from Class IX.7 at SMP Negeri 1 Pinrang. Data were collected through creative thinking ability tests, student response questionnaires, and observation sheets of the learning implementation. The results showed a significant improvement in students’ mathematical creative thinking abilities after the application of the PjBL-STEM model, with the average score increasing from 40.58 to 83.23 and an average N-Gain score of 0.71. A total of 60.61% of students reached the "very creative" category, while 39.39% were in the "creative" category. The paired sample t-test revealed a significant difference between pretest and posttest scores (p < 0.05). Thus, the integration of the PjBL model with the STEM approach proved to be effective in improving students’ mathematical creativity through contextual, collaborative, and meaningful project-based learning.